When Can Negativity Mean Success? Gender Composition, Negative Relationships and Team Performance. (August 2021) - Bradley, Bret; Henry, Sarah; Blake, Benjamin
Teams are often plagued by internal discord, such as negative relationships, which can impede successful team performance. While most teams eventually encounter negative relationships, we have limited knowledge on how teams manage this negativity. In this article, we expand scholarship on teams by exploring an inherent team characteristic, gender composition, to assess its role in how teams cope with negative relationships. On the one hand, social role theory suggests that teams comprised of more women will perform better in the presence of negative relationships. On the other hand, theories and evidence on personality and individual differences suggest that teams comprised of more men will perform better in the presence of negative relationships. We studied 151 student project teams, and found that teams of mostly women performed better than teams of mostly men, when negative relationships existed among team members. We discuss the implications of these findings for research and practice.